2021
DOI: 10.3389/fmed.2021.727965
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance and Integrative Analysis of the SMC Family in Hepatocellular Carcinoma

Abstract: Worldwide, hepatocellular carcinoma (HCC) is one of the most malignant cancers with poor prognosis. The structural maintenance of chromosomes (SMC) gene family has been shown to play important roles in human cancers. Nevertheless, the role of SMC members in HCC is not well-understood. In this study, we comprehensively explored the role of the SMC family in HCC using a series of bioinformatic analysis tools. Studies have demonstrated that the mRNA expression levels of SMC1A, SMC1B, SMC2, SMC4, and SMC6 are sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Structural maintenance of chromosomes protein 3 (SMC3) , a member of the chromosome structural maintenance family, helps to maintain chromosomal stability by forming heterodimers. SMC3 is highly expressed in HCC tissues and is positively correlated with poor prognosis in affected patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Structural maintenance of chromosomes protein 3 (SMC3) , a member of the chromosome structural maintenance family, helps to maintain chromosomal stability by forming heterodimers. SMC3 is highly expressed in HCC tissues and is positively correlated with poor prognosis in affected patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that immune cell infiltration affects tumor progression and recurrence while also playing an important role in determining the response to immunotherapy and clinical outcomes [29][30][31]. LUSC is a genetically complex and heterogeneous disorder with no effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The HPA ( https://www.proteinatlas.org/ ) is an online database that contains immunohistochemistry-based expression data for various cancer types [ 43 , 44 ]. In this investigation, we used immunohistochemical images to examine the levels of protein expression of several GATA members in KIRC tumors and normal kidney tissues.…”
Section: Methodsmentioning
confidence: 99%